(untitled) (Experimental biology, 2018)
In this work is submitted the systematic analysis of weed plants of flora of the Zerendinsky District of the Akmola region. In flora of the explored area have been revealed 84 species of the weed plants relating to 70 species and 29 families. By quantity of species the Asteraceae family is in the first place (18 species or 21,4%); on the second Poaceae (8 species or 9,5%), on the third Fabaceae (7 species or 8,3%). Further the Scorphulariaceae Juss families have been settled down – 5 species. Boraginaceae Juss аnd Rosaceae Juss. – 4 species. Brassicaceae Burnett., Caryophyllaceae Juss., Geraniaceae Juss., Polygonaceae Juss. –3 species. Apiaceae Lindl., Chenopodiaceae Vent., Lamiaceae Lindl., Plantaginaceae Juss., Ranunculaceae Juss., Urticaceae Juss. – 2 species and other families have 1 species. By the results of the carried-out ecological analysis in relation to humidity of the soil weed plants were subdivided as follows: mesophytes – 37 species, kseromesophytes – 21 species, kserophytes – 10 species, gigrophytes – 6 species, mezokserophytes – 5 species, gigromesophytes – 4 species and mesogigrophytes – 1 specie. There are 37 species of the weed plants belong to mesophyta. They belong to the 14 families. The Asteraceae Dumort families (12 species) prevail among them by the quantity of species. Poaceae Barnhart (5 species), Fabaceae Lindl (4 species), then Geraniaceae Juss follow (3 species), Brassicaceae Burnett., Polygonaceae Juss., Scrophulariaceae Juss. (2 species), and Apiaceae Lindl., Rosaceae Juss., Urticaceae Juss., Plantaginaceae Juss. And Boraginaceae have 1 species. There are 21 species of the weed plants in kserofita. They belong to the 15 families. There are 10 species of the weed plants in kserofita. There are 6 species in gigrofita. They belong to the 6 families. There are 5 species in mezokserofita which belong to the 4 families. There are 4 species in gigromezofita which belong to the 4 families. On the system of classification of K. Raunkier (1905) weed plants have arranged as follows: gemirhbgnjfita (56 species or 66,67%), terofita (16 species or 19,5%), kriptofita (7 species or 8.33%) and khamefita (5 species or 5,95%). Weed plants of the explored area on character of nutrition belong to not parasitic plants. Among juvenile weed plants on the vegetative period were divided into spring – 12 species (14,29%), wintering – 5 species (5,95%) and biennials – 8 species (9,52%). There are 24 species (28,57%) of rod root plants, 26 species (30,95%) of rootstock weeds, 7 species (8,33%) of stem sucker, 2 species (2,38%) of fibril among perennial weed plants.